Formation of the brazilian State: between patrimonialism and developmentalism - Lima, Matheus Silveira (Laboratório Editorial Faculdade de Ciências e Letras, 2019)
This paper presents an important debate that connects reflections of sociology with that of economic theory based on the same theme: the role of the state in Brazil and the importance of Portugal's heritage. We will sociologically analyze the connection between the patrimonialist political construction and the emergence of commercial capitalism, which results in a blockade of democracy and state modernization, and from an economic perspective, the approach of the same theme of the state as a driver of development throughout the century. XX, until the 1980s, when the strategies of growth and modernization from the developmental bias lose strength, becoming increasingly oriented towards a market economy.